DEKADENSI MORAL DI KAMPUNG SAMBUNG AYAM DESA PABUARAN KECAMATAN PABUARAN KABUPATEN SERANG PROVINSI BANTEN - Arifin, Zaenal; Abdul Kudus, Wahid (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
The purpose of this research is to describe moral decadence in the chicken-fed village in the Pabuaran community, Pabuaran sub-district, Serang district, Banten province. The approach used is qualitative with the type of case study research. The research location is located in Indonesia. The results of the study show that: moral decadence in Kampung Connect Ayam is often carried out by men, aged 20-50 years and working, educated Players range from elementary to high school/vocational school, player betting intensity in one or two months, 4-12 times and cock games. Players Can use their own fighting cocks or bet on other people’s cocks. Second, how to play cockfighting gambling consists of several stages, namely preparation, implementation and completion. The preparatory stage consists of players or chicken owners looking for or determining enemies and determining locations. The next step is execution, at this execution stage the cocks fight each other for 90 minutes, consisting of 6 circles. In the final phase, the cock loses or wins And the distribution of the betting funds. The chicken that is usually played in cockfights is the male Bangkok chicken. Third, the gambler who connects the chicken usually carries out the action with friends and neighbors, meanwhile the money from the bet is used to have fun, get drunk and fulfill their daily needs.